Adolescent employment, family income and parental divorce. (April 2023) - Herbst-Debby, Anat; Kaplan, Amit; Endeweld, Miri; Achouche, Noa
Abstract: The study examines the relation between parental family status, family income and three aspects of adolescent employment: the likelihood to be employed, the adolescent's earnings and the share of the adolescent's earnings as part of family income. While the relation between parental divorce and adolescents' outcomes has been widely studied, the relation between parental divorce, family income and the adolescent's employment has received less attention. Based on longitudinal administrative data on 12–17 year olds (n = 4023), results showed that adolescents whose family had a medium income level and those experiencing parental divorce had higher employment rates. Once employed, adolescents from the lowest household income level had higher earnings and contributed a higher share of household income than adolescents from the middle and top levels. While experiencing parental divorce was unrelated to adolescents' earnings, it did increase their contribution to household income compared to peers from intact families. The combination of parental divorce and low family income increased the adolescent's share compared to less vulnerable socioeconomic groups. The study proposes another mechanism of coping with low family income in general and with the negative economic consequences of union dissolution in particular: the adolescent as third breadwinner.